Juvenile Justice in the Republic of Kazakhstan – prospects (Journal of actual problems of jurisprudence, 2019)
The article discusses issues concerning development of court practice on the effectiveness of policies and practices of administrationof juvenile justice requires coordinated work of the judiciary and relevant government and non-government bodies and publicorganizations